Treatment of Cutaneous Warts With Multiple Puncture Technique - Mclaughlin, Joseph S. (Hand (N Y), 2018)
Background: Despite a multitude of treatment options, cutaneous warts on the hands can be a recalcitrant clinical problem. Methods: Based on Current Procedural Terminology (CPT) billing codes, the office database was searched for a 10-year period of warts treated with a puncture technique after institutional review board approval. Office notes were examined, and patients were contacted to assess wart resolution or the need for further treatment as well as any complications. Results: Of 16 patients who were identified with the treatment and diagnosis, 13 were able to be contacted. Median time to resolution was 22 days with a range of 10 to 30 days. Median size was 10 mm, range of 6 to 20 mm. Patients ages ranged from 7 to 88 years. Symptom duration prior to treatment was a median of 16 months, range of 5 to 48 months. Follow-up median was 6 years, range of 2 to 156 months. Three patients were less than 1 year from treatment, all others had follow-up more than 4 years. Complete resolution was seen in 11 patients (85%). Four patients had resolution of other warts in the local area who were not treated with puncture. Three patients had resolution of untreated warts at distant sites. Other than local tenderness, there were no complications. Conclusions: Barbotage, the multiple puncture of cutaneous warts, may be a reasonable treatment with minimal morbidity.